Implementation of SVM for five-level cascaded H-Bridge multilevel inverters utilizing FPGA - Maher Abd Ibrahim Al jewari; Auzani Jidin; Siti Azura Ahmad Tarusan; Mohammed Rasheed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The Space Vector Modulation SVM technique has won large acceptance for AC drive applications. However the utilization of multilevel inverters connected with SVM by Digital signal processor (DSP) raise the intricacy of control algorithm or computational load, increases of the obtaining distortions output voltage. The development of SVM in multilevel inverters may offer higher numbers of switching vectors for acquiring further enhancements of output voltage performances and implement by using Field Programmer Gate Array (FPGA), investigate lower Total Hormonic Distortion (THD). This paper reports the performance evaluation of SVM for five-level of Cascaded H-Bridge Multilevel Inverter CHMI using MATLAB/Simulink, which is sampled at the minimum sampling time, i.e. DT = 5 μs. The switching signals for driving insulated gate bipolar transistor (IGBTs) which are stored in MATLAB workspaces, are then used to be programmed in FPGA using a Quartus II software. Which can be stated the lower THD of the simulation result is about 14.48% for five-level CHMI and experiment result is about 14.31% for five-level CHMI at modulation index M_i=0.9. The error percentage between the simulation results and experimental results of the fundamental output voltage in SVM is small which is approximately less than 1 %.